Assessment of Sublethal Effects of Neonicotinoid Insecticides on the Life‐History Traits of 2 Frog Species. (6th August 2019) - Robinson, S.A.; Richardson, S.D.; Dalton, R.L.; Maisonneuve, F.; Bartlett, A.J.; de Solla, S.R.; Trudeau, V.L.; Waltho, N.
Abstract: Neonicotinoid insecticides are used extensively in agriculture and, as a consequence, are now detectable in nearby aquatic environments. Few studies have evaluated the effects of neonicotinoids on amphibians in these aquatic environments. In the present study, we examined the effects of 2 commercial formulations of neonicotinoids (active ingredients clothianidin and thiamethoxam) on survival and life‐history traits of wood frogs ( Lithobates sylvaticus ) and northern leopard frogs ( Lithobates pipiens ). We used artificial pond mesocosms to assess the effects of these neonicotinoids, at nominal concentrations of 2.5 and 250 µg/L, on amphibian larval development through metamorphosis. We found no differences between controls and neonicotinoid exposure for any of the endpoints assessed for either wood frogs or leopard frogs. The present study suggests that concentrations meeting or exceeding observed levels of clothianidin and thiamethoxam in surface waters will not directly affect metamorphosis in 2 amphibians. Environ Toxicol Chem 2019;38:1967–1977. © 2019 Her Majesty the Queen in Right of Canada. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.